The case of N.P. Vitvitsky, V.A. Gussev, A.W. Gregory, [a.o.], charged with wrecking activities at power stations in the Soviet Union. Heard before the special session of the supreme court of the USSR. In Moscow, April 12-19, 1933. Transl. of the official verbatim report (State Law Publishing House, 1933)
I. Sessions of April 12 and 13, 1933. 291 p.